The value of the function f(6 + h) − f(6) is 6(6 + h) -(6 + h)^2
The equation of the function is given as:
f(x) = 6x -x^2
The function is given as:
f(6 + h) − f(6)
This means that x = 6 + h and x = 6
f(6 + h) = 6(6 + h) -(6 + h)^2
f(6) = 6(6) -(6)^2
So, we have:
f(6 + h) − f(6) = 6(6 + h) -(6 + h)^2 - 6(6) + (6)^2
Evaluate the like terms
f(6 + h) − f(6) = 6(6 + h) -(6 + h)^2
Hence, the value of the composite function f(6 + h) − f(6) is 6(6 + h) -(6 + h)^2
Read more about functions at:
https://brainly.com/question/10687170
#SPJ1